Exploring the therapeutic mechanism of curcumin in spinal cord injury treatment based on network pharmacology, molecular dynamics simulation, and experimental validation - He, Yongzhi; Lu, Jiachun; Luo, Yushan; Pang, Rizhao; Hu, Xiaoming; Ding, Lijuan; Xiao, Hua; Wang, Yunyun; Wang, Wenchun (Frontiers in Chemistry, 2025)
IntroductionCurcumin, a natural active compound derived from plants, is widely used as a pigment across the globe. Research has demonstrated that curcumin possesses neuroprotective properties in spinal cord injuries (SCIs); however, its specific mechanisms of action remain unclear. This study aimed to elucidate the potential mechanisms underlying curcumin’s therapeutic effects in SCI.MethodsWe screened the targets of curcumin in the treatment of spinal cord injury using network pharmacology across a variety of public databases. The interaction between the compound and the target was analyzed through bioinformatics analysis, molecular docking, and molecular dynamics simulation. Finally, the prediction results were verified by simulating spinal cord injury through oxygen–glucose deprivation (OGD) injury in PC12 cells.ResultsInitial screening indicated 13 core targets involved in mitigating SCI. Curcumin may regulate the HIF pathway, immune cells, inflammation, oxidative stress, and other processes. Matrix metalloproteinase-9 (MMP9), tumor necrosis factor (TNF), interleukin-1β (IL-1β), signal transducer and activator of transcription 3 (STAT3), and caspase 3 (CASP3) were identified as key targets of curcumin in SCI regulation. Molecular docking results demonstrated that curcumin exhibited favorable affinity with the core targets, with MMP9 showing the highest binding affinity (−8.76 kcal/mol). Further studies confirmed that curcumin stably binds with MMP9, and the binding site was located at residues 220–225. Cell counting kit-8 (CCK8) assay results showed that curcumin exerted a good therapeutic effect. Western blot results showed that curcumin inhibited the expression of MMP9 protein but had no significant effect on the expression of TNF-α.ConclusionCurcumin exerts its effects on SCI through multiple targets and pathways. Its specific mechanisms involve the inhibition of inflammation, prevention of apoptosis and ferroptosis, and promotion of neuronal repair. MMP9 may be a key target mediating curcumin’s protective effects against SCI. These findings provide scientific evidence for further research and development of drugs.